Securing future-fit jobs in the green transformation: A policy framework for industrial policy - Jakob Hafele; Laure-Alizée Le Lannou; Nils Rochowicz; Sonia Kuhls; Claudius Gräbner-Radkowitsch (ZOE. Institut für zukunftsfähige Ökonomien, 2023)
Achieving compatibility between economies and planetary boundaries poses a momentous challenge. It requires a fundamental restructuring of current industrial systems, with a dual focus on the creation and protection of green technologies and firms, as well as the redirection of workers and technologies from ecologically harmful activities to support sustainable production patterns. This paper acknowledges that during the process of green industrial restructuring, certain non-future fit sectors will inevitably decline due to regulatory requirements or reduced competitiveness. Allowing market forces to solely determine the decline of these sectors would result in extensive economic and social consequences. Instead, this paper advocates for the implementation of active industrial policies to facilitate the phasing out of non-future-fit sectors and to ensure a just transition for the workers affected. To this end, the paper introduces a data-driven political framework with two objectives: 1) identify emission-intensive sectors with limited potential to stay competitive (non-future-fit sectors) and 2) identify sectors capable of absorbing workers from declining sectors while presenting better economic potential (complementary future-fit sectors). Despite the data limitations, applying this framework in Germany and Hungary reveals two significant challenges. First, the results indicate a limited number of skill-related sectors able to absorb workers from declining industries, highlighting the reluctance of workers to adapt to the changing landscape due to the costs associated with retraining and relocation. Second, a market-driven approach to the green transformation is likely to result in gradual shifts, requiring ongoing worker retraining as other problematic sectors decline. These preliminary findings underscore the need to anticipate these challenges and prioritise worker retraining and skill development, particularly in cases where there are limited complementary future-fit sectors.
Keywords: 330; Green Transformation; Industrial Policy; Competitiveness; Emission Intensity; Economic Complexit